Moral Development Methods in Shaping Student Behavior at MTs PAB 2 Sampali - Nabila Haryati (-, 2023)
The aims of this research are 1) to describe and determine the method of moral inculcation in shaping the behavior of the students of MTs PAB 2 Sampali. 2) to find out the problems of moral education in the development of student behavior at MTs PAB 2 Sampali. The results of this study are expected to enrich scientific treasures and become a reference for every teacher in their role in the teaching and learning process and can be input for all parties who are competent in the field of education, especially this research is a field study. The subject of this research is the method of forming student behavior at MTs PAB 2 Sampali to improve morale. The results of the study showed that MTs PAB 2 Sampali educational methods for the formation of student behavior with the story method, the sample method, the practical method, the demonstration method and the reward and punishment method. The problems faced to improve morale are; consists of external factors and internal factors. External factors are globalization and the flow of information, internet available in villages, high cost of living, lack of religious organizations. Though the problem itself is; low input (input) madrasah, socio-economic conditions of parents, education management that is not optimal, enthusiasm and motivation to learn students who are not optimal.